Organizational Factors, Teachers' Professional Development and Teaching Practices: Findings From Female Elementary School Teachers - Naveed R. Khan; Sana Zaidi; Najmunnisa Khan (Institute of Business Management, 2018)
Development of teaching competencies has always considered the most prolific dimension in teaching education. It assists teachers in teaching and in preparing to adopt more functional orientation practices beneficial towards teaching practice. This study aimed to investigate the antecedents of teachers' teaching practices. Primary data through survey was collected from 377 female elementary school teachers from private sector schools based in Karachi. Smart PLS was used for data analysis. Findings of this study revealed a significant relationship among organizational factors, teachers' professional development and teachers' teaching practices. This paper contributes to existing knowledge by reporting new empirical evidences from female elementary school teachers. Hence, this research provides practitioners and policy makers with better insights into some practices that could improve teaching practices.